2016
DOI: 10.17554/j.issn.2224-3992.2016.05.603-1
|View full text |Cite
|
Sign up to set email alerts
|

Putative Prophylaxes of Aloe Vera Juice with L-arginine to Chronic Fatigue Syndrome

Abstract: L-Arginine is one of the most metabolically versatile amino acids. Several in vitro/in vivo experiments have indicated that exogenous L-arginine intake has multiple beneficial pharmacological and pharmaco-kinetic effects. Such effects include reduction in the risk of vascular and heart diseases and chronic fatigue syndrome. The effects of a dietary supplementation of aloe vera juice with L-arginine to chronic fatigue syndrome were demonstrated and a questionnaire was given to adult subjects. The questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Case reports on w-3PUFA, L-Arginine and AVJ supplement to PD patient with/without diabetes showed that the PD patients at the stage 3 showed possible remission in movements by treatment of PD-drug, 3-w PUFA and L-Arginine supplement with AVJ. The benefits of AVJ with L-Arginine to chronic fatigue languid syndrome, constipation and muscle pains on adult subjects were reported in previous paper [52] .…”
Section: Case Reports Of Aloe Vera Juice With W-3 Polyunsaturated Fatmentioning
confidence: 59%
“…Case reports on w-3PUFA, L-Arginine and AVJ supplement to PD patient with/without diabetes showed that the PD patients at the stage 3 showed possible remission in movements by treatment of PD-drug, 3-w PUFA and L-Arginine supplement with AVJ. The benefits of AVJ with L-Arginine to chronic fatigue languid syndrome, constipation and muscle pains on adult subjects were reported in previous paper [52] .…”
Section: Case Reports Of Aloe Vera Juice With W-3 Polyunsaturated Fatmentioning
confidence: 59%
“…Liu and Tang [21] presented the role of DNA methylation, post-translational modification of histones, adenosine triphosphate-dependent chromatin conformation and remodeling, and non-cording RNAs in HF pathophysiology. The authors reported epi-transcription [6,7] ; Control of the NO/ONOO-cycle as the central cause of heart failure [8] ; Efficacy of aloe vera gel with L-arginine on nitro oxide production [9] ; Prophylaxes of aloe vera gel juice alone or the juice with L-arginine to chronic fatigue syndrome [10] and with CoQ 10 to enhance muscle performance [11] in a survey of a large number of subjects by questionnaire.…”
Section: Epigenetic Regulation Of Heart Failurementioning
confidence: 99%